How Does AI Support Continuing Medical Education? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Artificial intelligence (AI) is rapidly transforming various aspects of our lives, and the field of medicine is no exception. From diagnostics to drug discov...
Keywords: AI in Medical Education and Future of Healthcare; Support; Continuing; Medical; Artificial Intelligence; Healthcare; Diagnostics